Chylous Leakage After Breast-Conserving Surgery and Axillary Clearance: Case Report and Management Strategies - Yin, Liang; Chen, Peiqing; Agyekum, Enock Adjei; Xiao, Xiudi; Qian, Xiaoqin (Frontiers in Oncology, 2022)
Chylous leakage is a rare complication of breast and axillary surgery. We present a case of chylous leakage inside the breast following breast-conserving surgery and axillary lymph node dissection. The majority of chylous leakages in the breast are managed with conservative measures aimed at reducing lymphatic fluid production and outflow. Surgical intervention is required in cases of conservative treatment failure and high output chylous leakage. To the best of our knowledge, this is the first case report of chyles leaks inside the breast following breast-conserving surgery that was successfully treated surgically.